Mitigating contamination from food processing - Birch, Catherine S.; Bonwick, Graham A. (Food chemistry, function and analysis ;, 2020)
Methods for identification and measurement of existing and newly discovered contaminants are required, especially those that are cheap, simple and rapid, so that testing may be more frequent within the food supply chain. This book examines the formation of toxic compounds during the processing of food and strategies to mitigate their creation. Modification of process conditions can reduce the health risks posed by these compounds to consumers. This new volume will update knowledge on current methods for mitigation of these process contaminants and is aimed at industrialists in food processing, academic researchers and graduate students studying food science and technology or food engineering